MILD combustion of hydrogen and air – An efficient modelling approach in CFD validated by experimental data. (29th January 2022) - Mayrhofer, Markus; Koller, Michael; Seemann, Peter; Bordbar, Hadi; Prieler, Rene; Hochenauer, Christoph
Abstract: The present work deals with the development of an efficient modelling approach for the flameless combustion of pure hydrogen with highly preheated air. It contains an application of different flamelet-based combustion models to achieve convergence in a computationally cheap way in contrast to time consuming methods such as the Eddy Dissipation Concept (EDC) model. Moreover, an evaluation of three detailed reaction mechanisms for the application of flameless hydrogen combustion is also included. The selection and implementation of a "Weighted Sum of Gray Gas" (WSGG) model to predict the radiative heat transfer as accurate as possible constitutes another important goal in the present work. The results of all modelling approaches were compared with extensive temperature measurements in the reaction zone. Additional temperatures of the test rig's control thermocouples were also compared with the results of the simulation to strengthen the validation. Maximum temperature deviation in the burner's axis of about 50 K can be achieved. Furthermore, the experimental and numerical results in this paper were compared with the results of flameless combustion of natural gas at equal furnace conditions and the same burner test rig. Higher temperatures in the burner axis up to a distance of 1855 mm were observed at hydrogen operation with a maximum difference of about 150 K to the natural gas case. A concluding evaluation of the furnace efficiency showed an increase by about 7% by changing the fuel from natural gas to hydrogen. This is achieved by reduced flue gas loss and an improved heat transfer. Highlights: Efficient CFD approach for flameless hydrogen combustion. Evaluation of flamelet-based combustion models. Implementation of different extended WSGG model approaches. Validation with extensive experimental data. Comparison of natural gas and hydrogen as fuel for MILD combustion.